Влияние места расположения намагничивающих обмоток преобразователя на гармонический состав поля - Горкунов, Борис Митрофанович; Борисенко, Евгений Анатольевич; Львов, Сергей Геннадьевич; Шибан, Тамер (НТУ "ХПИ", 2019)
В данной работе рассмотрен первичный электромагнитный преобразователь с неоднородным зондирующим полем структура которого представлена в виде пространственно-периодических гармоник. Для исключения влияния на результат измерения высших гармоник и выделения необходимых информативных гармоник предложено несколько различных систем намагничивающих полюсов преобразователя что позволило выделят необходимые сочетания четных или нечетных гармоник выходного сигнала преобразователя и повысило точность многопараметрового контроля электрических, магнитных и геометрических параметров исследуемых изделий. Выполнен расчет и показано влияние высших гармоник поля на выходные сигналы в измерительных обмотках преобразователя.

In this paper, we consider a primary electromagnetic transducer with an inhomogeneous probe field whose structure is represented as spatially periodic harmonics. The number different systems of magnetizing poles of the transducer was proposed in order to eliminate the higher harmonics effect on the measurement result and to highlight the required informative harmonics. This made it possible to select necessary combinations of even or odd harmonics of the transducer’s output signal and to increase the accuracy of the multi-parameter control of the products under study. It was performed calculation and the effect of the field higher harmonics on the output signal in the transducer’s measuring windings was shown. It was proposed to estimate the value of the error caused by other harmonics elimination when calculating as the ratio of the first harmonic amplitude to the algebraic sum of the EMF of this eliminated and accounted harmonics. It was established that for a transducer with one exciting winding, elimination the third harmonic results in an error calculation of the resulting EMF of 5%, and the calculation error for a transducer with two exciting windings associated with elimination of the fifth harmonic is 1.5%.
The influence of the transducer’s magnetizing windings location on the harmonic composition of the field
Keywords: вихретоковый измерительный преобразователь; пространственно-периодическая структура поля; неразрушающий контроль; цилиндрические металлические изделия; non-destructive testing; spatial-periodic field structure; cylindrical metal products